Helen Sistem Informasi Kepegawaian Pada PT Perkebunan Mitra Ogan - Gultom, Helen Tri Anggraini; Amelia Fransen, Lisa (Universitas Multi Data Palembang, 2024)
PT Perkebunan Mitra Ogan, a company in the agroindustry sector specializing in the cultivation of oil palm and rubber, with a workforce of 52 employees. Despite implementing a computerized system for HR data management, there are still shortcomings in employee data management and storage. To address this issue, a web-based employee information system has been developed with the aim of improving efficiency and reducing the risk of errors and data loss. The method used in developing this system is RUP (Rational Unified Process), with design carried out using Visual Studio Code, MySQL, and the Laravel framework with PHP programming language. With the implementation of this system, the company can manage employee data, recruitment processes, attendance, leave requests, assignments, disciplinary actions, rewards, and termination processes.